Human Intelligence Cultivation with the 2CG® Poetry Machine: How to Boost Future Skills Development and Idea Generation with Artistic Impulses in Lab 21 - Merl, Christina (International Journal of Advanced Corporate Learning (iJAC), 2022)
Acquiring pure fact-based knowledge is no longer sufficient when it comes to dealing with increasingly complex realities in the machine age, such as the degrowth economy, climate change and global health crises. 21st century learners who want to interact with the world in a constructive way need to cultivate (human) capabilities, develop relevant practical skills and acquire relational knowledge, which implies that they can apply factual knowledge in diverse contexts so as to solve complex problems. The present paper aims to demonstrate how the 2CG® Poetry Machine, a hybrid coaching tool that makes use of artistic impulses, can support learners across cultural, hierarchical and disciplinary boundaries in developing future skills and generating new ideas. The focus is on communication skills, critical thinking skills, creativity and imagination, collaborative skills and ICT literacy. Practice examples are given to show how the 2CG® Poetry Machine uses impulses from poetry, puppetry, literature, theater, photography, dance and music to enable learners to connect with their creative power, improve their skills and generate new ideas in Lab 21, a hybrid hyper-structure for learning, sharing and exploring new ways of thinking and doing.